Strategic planning for success : aligning people, performance, and payoffs - Kaufman, Roger A.; Oakley-Browne Hugh; Watkins Ryan; Leign Doug (San Francisco : Jossey-Bass/Pfeiffer, 2003)
Offers you a pragmatic guide to the design and development of practical and pragmatic strategic thinking and organizational alignment that will yield high-impact results and measurably add value to you, your organization, your clients, and society. Unlike other books on the topic, this volume goes beyond simply detailing the tools and techniques of design and development by clearly showing how to align what you do with what will be most valuable to all stakeholders.
Includes bibliographical references (p. 363-371) and index.
oif 12/03/15
Loan
Keywords: Strategic planning; Organizational performance